Formulation and Evaluation of Candesartan Cilexetil Fast-Dissolving Tablets Using Natural Superdisintegrant (Asian Journal of Pharmaceutics (AJP), 2023)
Introduction: Candesartan Cilexetil is a BCS class II drug having low water solubility, which can be enhancedby formulating them in to solid dispersions by using hydrophilic carriers and compressed in to fast dissolvingtablets by using natural superdisintegrants. Materials and Methods: The solubility and dissolution rate ofCandesartan Cilexetil were aimed to be increased in this investigation by employing fusion process to create asolid dispersion with a hydrophilic carrier like PVP or PEG 6000. Additionally, utilising Croscarmelose sodium(CCS) and Aegle marmelos as superdisintegrants, the solid dispersion was compressed into fast dissolving tablets.Results and Discussion: The drug release increased proportionately with increase in carrier concentration.Among the solid dispersions prepared, the one made with PEG6000 released the medication more rapidlythan the one made only with PVPK30 and pure drug. First order kinetics were found to determine the release.Conclusion: The prepared solid dispersions were then mixed with super-disintegrants like Croscarmelosesodium (CCS) and Aegle marmelos to produce tablets. Such tablet formulations have been observed to releasedrug more rapidly than tablets prepared from pure drug. FTIR and XRD tests are used to characterise the puredrug and optimised formulation F6. Results showed that there were no drug and excipient interactions.